Association Between Socio-Emotional Health, Physical Activity and Screen Time Among Children. - Aliyas, Zeinab; Mahmoudian, Armin; Cloutier, Marie-Soleil (American Journal of Health Education)
Background: Technological advancements have led to increased screen time and decreased Moderate to Vigorous Physical Activities (MVPA) among children. The impact of MVPA on children's mental health is less explored compared to adults. Purpose: This study investigated the relationship between children's social-emotional health, MVPA, and screen time across different socioeconomic statuses (SES) in Bandar Abbas, Iran. Methods: Primary school children completed questionnaires (n = 1041), analyzed for MVPA, screen time, and emotional health indicators. Results: Lower SES children showed higher MVPA levels (23.11% active) than higher SES counterparts (11.8% active), but higher SES children exceeded 2 hours of screen time more (58.7% vs. 44.5%). Happiness correlated positively with MVPA, while worries negatively impacted MVPA. Sadness and worries increased screen time. Discussion: Poor socio-emotional health was linked to increased screen time and decreased MVPA, limiting physical activity opportunities. Significant SES disparities suggest tailored interventions are crucial. Translation to Health Education Practice: Addressing socio-emotional well-being is vital for promoting healthier lifestyles among Iranian children, emphasizing strategies to mitigate screen time and enhance MVPA.